DEGRADASI SENYAWA METANIL YELLOW SECARA FOTOKATALITIK MENGGUNAKAN TiO 2 DAN HNO3 - Azkia Alma Ayesha; Akmal Mukhtar; Pepi Helza Yanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Photocatalysis with TiO2 -UV can be used to reduce the content of waste dye in the water. Degradation of metanil yellow solution had been done by photocatalytic using TiO2 as catalyst and HNO3 as an oxidator. Photocatalytic method used radiation of 30 watt UV light with λ = 437 nm. Degradation of metanil yellow was done with several reaction parameters such as time of radiation reaction, mass of TiO2 , and addition of HNO3. The result of this research showed that metanil yellow 10 ppm have degraded 30,755% after 120 minutes radiation, wheareas with similiar consentration by addition 0,008 mass of TiO2 degraded 54,689% with radiation time up to 45 minutes. HNO3 as an oxidator in degradation without UV radiation can affect the percentage rate of degradation.